Residual cone vision without alpha-transducin. - Stockman, A; Smithson, H; Michaelides, M; Moore, A; Webster, A; Sharpe, LT (2007)
Behavioral experiments in humans with a rare genetic mutation that compromises the function of alpha-transducin (Galpha the alpha-subunit of the G-protein in the primary cone phototransduction cascade) reveal a residual cone response only viable at high light levels and at low temporal frequencies. It has three characteristic properties. First, it limits temporal frequency sensitivity to the equivalent of a simple first order reaction with a time constant of approximately 140 ms. Second, it delays the visual response by an amount that is also consistent with such a reaction. Third, it causes temporal acuity to be linearly related to the logarithm of the amount of bleached pigment. We suggest that these properties are consistent with the residual function depending on a sluggishly generated cone photobleaching product, which we tentatively identify as a cone metarhodopsin. By activating the transduction cascade, this bleaching product mimics the effects of real light and is therefore one of the molecular origins of "background equivalence," the long-established observation that the aftereffects of photopigment bleaches and the effects of real background lights are equivalent. Alternative explanations for the residual cone response include the possibilities that there is a secondary phototransduction mechanism that bypasses alpha-transduction, or that the truncated alpha-transduction that results from the mutation retains some minimal functionality.